"If he is dying, he must be alive": Demetaphorising Cancer through Pentadic Analysis of Dattani’s Brief Candle - Chatterjee, Nilanjana (Summerhill IIAS Review, 2025)
This study identifies the metaphors of illness related to cancer and cancer-related death in Dattani’s Brief Candle: A Dance between Love and Death (2010) to demetaphorise the language of cancer and thereby destigmatize cancer patients in the Indian context. In the post-pandemic era, when the critics are resisting and redefining languages of illness to live a bit better or healthier in a world wherein disease is inevitable, it is necessary to reconsider the illness metaphors attached to cancer wherein the patient becomes the disease. For this, the study is divided into four sections: Section I situates Sontag’s (1977) Illness as Metaphor to understand why illness language related to cancer must be demetaphorised. Section II explicates how Burke’s pentadic analysis can be used as a meaningful tool to identify metaphors of illness in Dattani’s Brief Candle: A Dance between Love and Death. Section III makes a pentadic study of the play to metaphorize cancer. Thef inal section thereby concludes. The study is unique as serious academic work on either Dattani Studies or Medical Humanities has under-noticed Dattani’s text in demetaphorising cancer to live cancer more healthily and if possible, to celebrate the disease when ‘nothing to be done.’